Bisphenol A in Odontology: recent data - Vautherin, Thomas (2020)
Background and Objective: Bisphenol A (BPA) is an organic compound of the aromatic family used mainly as a monomer, for more than 50 years in the production of polycarbonate plastics and epoxy resins. Nowadays, bisphenol A is a worrying substance that deserves special attention. The goal of this work is to focus on bisphenol A and its biological effects on the human body. Methods: A bibliographic search was performed in databases such as PubMed, b-On and Elsevier. The keywords used were: "Bisphenol A", "BPA", "Endocrin Disruptor Chemicals". Results: There are several known effects on the human body resulting from the exposure to BPA such as in the reproductive system, dentition, brain, behavior, cardiovascular and in immune systems. In the oral cavity, dental composites release bis-GMA and BPA immediately after placement but released doses are usually too low to lead to biological effects. Conclusion: There are other materials such as silorans, Ormocer® and ionomer glass cements that can be good alternatives. Clinical studies are still neaded to prove that these materials are better than the composites, being these ones still the most used materials in conservative dental medicine.